Representation of Religious Moderation Values in Arabic Language Textbooks of Madrasah Aliyah: Insights from the Ministry of Religious Affairs of the Republic of Indonesia - Fikri, Ahmad Futunul; Khofifah, Khofifah; Fauziah, Fauziah; Muhajir, Muhajir (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Although much research has been conducted on the representation of religious moderation values in textbooks, there are still few who study it from the perspective of Arabic textbooks. Thus, this research aims to examine the representation of religious moderation values in the Madrasah Aliyah Arabic language textbook for class XI: insights from the Ministry of Religion of the Republic of Indonesia. This research uses a library research design with a qualitative approach. The research results show that the content of the Arabic textbook consists of 6 chapters covering shopping, health, travel, Hajj and Umrah, information and communication technology, and religion in Indonesia. The values of religious moderation in the class XI Arabic textbook are on page 57 with the theme